2006
DOI: 10.1111/j.1365-2958.2006.05319.x
|View full text |Cite
|
Sign up to set email alerts
|

The sugar phosphotransferase system of Streptomyces coelicolor is regulated by the GntR‐family regulator DasR and links N‐acetylglucosamine metabolism to the control of development

Abstract: SummaryMembers of the soil-dwelling, sporulating prokaryotic genus Streptomyces are indispensable for the recycling of the most abundant polysaccharides on earth (cellulose and chitin), and produce a wide range of antibiotics and industrial enzymes. How do these organisms sense the nutritional state of the environment, and what controls the signal for the switch to antibiotic production and morphological development? Here we show that high extracellular concentrations of N-acetylglucosamine, the monomer of chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
270
1
5

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 194 publications
(284 citation statements)
references
References 53 publications
8
270
1
5
Order By: Relevance
“…This effect is absent in a mutant defective in GlcNAc transport. 109 Therefore, transcription of nagE2 is induced by GlcNAc but repressed by DasR.…”
Section: Streptomycesmentioning
confidence: 99%
See 2 more Smart Citations
“…This effect is absent in a mutant defective in GlcNAc transport. 109 Therefore, transcription of nagE2 is induced by GlcNAc but repressed by DasR.…”
Section: Streptomycesmentioning
confidence: 99%
“…The effector molecule is GlcN-6-P, thus upon binding to GlcN-6-P, DasR is released from its target genes, 109 relieving the inhibition of antibiotic production and morphological differentiation. This effect is absent in a mutant defective in GlcNAc transport.…”
Section: Streptomycesmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the role of ubiquist molecules in signalisation has been poorly investigated, several studies confirmed that these molecules are likely to signal specific metabolic state and thus also play important regulatory roles (Viollier et al 2001a, b;Li et al 2008;Rigali et al 2008;Luti and Mavituna 2011). For instance, we have previously demonstrated that the peptidoglycan aminosugar building block N-acetylglucosamine (GlcNAc) has a different impact on development depending on the nutritional context and its concentration (Rigali et al 2006(Rigali et al , 2008Nothaft et al 2010;Craig et al 2012;Swiatek et al 2012).…”
Section: Discussionmentioning
confidence: 96%
“…Once regulatory DNA sequences have been demonstrated as targets for a specific transcription factor, their conserved signature is generally described by position weight matrices (PWMs) which specify the frequency distribution of nucleotides at each position of the TF cis-acting elements. Several PWMs based web tools (such as Target Explorer [1], Virtual Footprint [2], or PredictRegulon [3]) have directed experimental investigation by highlighting potential new target genes of a transcription factor [4], defining a regulon in closely related bacterial species, and also have contributed to revealing new cis-trans relationships [5]. The diversity and complexity of in vivo cis-trans relationships make computational predictions of transcription factors regulons hazardous.…”
mentioning
confidence: 99%